The professoriate and the post-truth era: A historiographic analysis of expert judgment and the destabilization of objective truth - Rachel E. Friedensen; Ezekiel Kimball (Arizona State University, 2018)
This paper explores the role that distrust of expert judgment plays in conservative critiques of higher education. We propose that academics should abandon the insistence on truth as the standard for the evaluation of research quality. Doing so would separate conservative critiques of higher education from broader concerns over expert judgment via the substitution of judgement criteria more readily accessible to laypeople. Based on evidence about how expert judgment actually functions, we propose utility as a standard accessible to all. We show this by describing a historiographic model of expert judgment within the research university. We close with a call for scholars to acknowledge the conflation of facts and values in their work-that is, its post-truth nature.